THE PHILOSOPHICAL WORLDVIEW OF MOLLANASRADDINSTS AS THE EMBODIMENT OF MODERNIST IDEAS IN AZERBAIJAN - Huseynov, Yusif (International Journal of Psychosocial Rehabilitation, 2020)
The article examines the irreplaceable role of the philosophical doctrine of mollanasradinsts in the early twentieth century in the dissemination of modernist ideas in Azerbaijan and the Caucasus, consisting of a synthesis of East and West, nationality and humanity from a socio-philosophical point of view. The author comments on the basis of factual materials and philosophical generalizations that the mullahs are famous for their modernist ideas, the values of the unity of tradition and innovation, as well as new, transforming concepts of society, state and personality.